Filsafat Logika Keilmuan Sebagai Landasan Integrasi-Interkoneksi Bimbingan Konseling Islam - Fuadi, Muhammad ikhsan; Irsyadunnas, Irsyadunnas (BINA' AL-UMMAH, 2025)
This study explores how the philosophy of scientific logic serves as the foundational basis for integration‑interconnection within Islamic Guidance and Counseling (IGC). By examining its epistemological and logical framework, the research reveals a holistic paradigm that harmonizes normative‑spiritual Islamic values with the rational‑empirical principles of modern counseling. Using a qualitative library research approach, key reference books, national and international journals, and relevant academic literature on the philosophy of science, logic, and IGC were purposively selected. The literature was identified, reviewed in depth, and analyzed through Creswell’s stages of qualitative analysis: deep reading for initial insight; coding of significant information units; thematic grouping of codes; and interpretation of themes to uncover the role of scientific logic in shaping an integrative and interconnected counseling paradigm. Findings demonstrate that framing IGC through the lens of scientific logic restructures the relationship between contemporary counseling methods and Islamic values. Addressing ontological, epistemological, and axiological dimensions ensures consistency, validity, and coherence, enabling counseling to engage clients’ psychological, spiritual, and cultural dimensions fully. Integration‑interconnection thus transcends technical combination, reconstructing IGC’s epistemological foundation to be holistic, transformative, and context-sensitive. The philosophy of scientific logic emerges as a strategic catalyst for developing a coherent and sustainable IGC framework.